2013
DOI: 10.1088/0004-637x/771/1/23
|View full text |Cite
|
Sign up to set email alerts
|

Two New Long-Period Hot Subdwarf Binaries With Dwarf Companions

Abstract: Hot subdwarf stars with F-K main sequence binary companions have been known for decades, but the first orbital periods for such systems were published just recently. Current observations suggest that most have long periods, on the order of years, and that some are or once were hierarchical triple systems. As part of a survey with the Hobby-Eberly Telescope, we have been monitoring the radial velocities of several composite-spectra binaries since 2005 in order to determine their periods, velocities, and eccentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Several long-period eccentric systems (with P ∼ 10 3 d) were recently discovered among sdB stars (Østensen & Van Winckel 2011, 2012Vos et al 2012Vos et al , 2013Deca et al 2012;Barlow et al 2012Barlow et al , 2013. Using new radial-velocity data collected with the HERMES/Mercator spectrograph (Raskin et al 2011), we show in this paper (Sect.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Several long-period eccentric systems (with P ∼ 10 3 d) were recently discovered among sdB stars (Østensen & Van Winckel 2011, 2012Vos et al 2012Vos et al , 2013Deca et al 2012;Barlow et al 2012Barlow et al , 2013. Using new radial-velocity data collected with the HERMES/Mercator spectrograph (Raskin et al 2011), we show in this paper (Sect.…”
Section: Introductionmentioning
confidence: 65%
“…We also include in Fig. 10 the sdB binaries with long periods (black crosses) from Østensen & Van Winckel (2011, 2012, Vos et al (2012Vos et al ( , 2013, Deca et al (2012), and Barlow et al (2012Barlow et al ( , 2013.…”
Section: The Evolutionary Context Of Ip Erimentioning
confidence: 99%
“…It is very unlikely that this variation is caused by the main-sequence companion. The solved orbits of sdB+MS binaries have long periods of the order of 1000 d (Vos et al 2012(Vos et al , 2013Barlow et al 2012Barlow et al , 2013. We therefore conclude that J205101.72+011259.7 is another candidate for a hierarchical triple system consisting of an sdB in a short-period binary with unseen companion and a main sequence star orbiting this inner binary with a long period (e.g.…”
Section: Hierarchical Triple Systemsmentioning
confidence: 79%
“…As argued in Clausen et al (2012), composite systems of the type sdB + early F could be crucial in determining the binary formation channel of hot subdwarfs, depending on the periods measured for these systems. Recently, in Barlow et al (2013) and Vos et al (2013), long period sdB+F/G systems have been reported. It would thus be interesting to know if our sample contains this type of binaries, and to make a follow-up study of them, determining their orbital parameters.…”
Section: Discussionmentioning
confidence: 99%